OPTIMALISASI POTENSI WISATA TELAGA SEMERU DALAM UPAYA PENGEMBANGAN EKOWISATA BERKELANJUTAN - Aini, Annisa Nur; Hanafi, Usman Bagus; Kurniawan, Moch Rizqi Bagus; Fahindra, Farizky Alif Owen; Hasbullah, Hasbullah; Mahfud, Lauhil Gilang Maulana; Sholihah, Mar’atus; Nuraini, Ayu Risma; Paramita, Virgin Diana; Aripratiwi, Ratna Anggraini (Jurnal Abdimas Sangkabira, 2024)
Semeru Lake is a bathing tourist attraction in Bulak Gempol Hamlet, Nguter Village, Pasirian District, Lumajang Regency. The cool air and clarity of the lake water attract tourists to visit. However, there is a lack of maintenance and attention from the community towards tourism management, especially regarding infrastructure around the lake. Also, the lack of support from the local village government makes it difficult for these baths to compete with other tourist attractions, hampering tourism's sustainability. Therefore, this service aims to revive the tourism potential of Semeru Lake and restore its attractiveness to tourists. This service uses the ABCD (Asset Based Community Development) method, which aims to empower the community and improve the quality of Human Resources (HR) by utilizing existing assets and potential. Through this method, it is hoped that empowerment can run evenly. As a result of the service, the service team improved by installing photo spots and providing rubbish bins to support optimal sustainable tourism management.